STUDY MECHANISMS OF LOW PROTEIN DIET SUPPLEMENTED WITH KETOANLOGS ON REDUCING PROTEINURIA AND MINTINING NUTRITIONAL STATUS IN TYPE2 DIBETIC NEPHROPTHY - Ting Dong; Weijie Yuan; Jialin Wang; Lijie GU (The Korean Society of Nephrology, 2012)
Diabetic nephropathy is one of the most important causes of end stage renal disease (ESRD) in the world. Recently in a multicenter, randomized clinical trial performed in China, it was found that compound α-keto acid tablet in combination with low protein diet(LPD+KA) reduced proteinuria and delayed the progression to ESRD in Type 2 diabetic nephropthy(T2DN). However, the mechanisms underlined these effects were not been elucidated. This study is a part of the continuation of the study to explore the effects of LPD+KA on podocyte as well as on local RAS in the kidney. A total of 60 patients with T2DN and CKD stages 3-4 are included in this study. All patients are treated with a LPD containing 0.6g protein/kg BW per day and 120-125 kJ/kg BW per day. The diet is randomly supplemented with keto-amino acids (Ketosteril®, Fresenius Kabi) at a dosage of 100 mg/kg BW per day. The other 30 patients receive placebo. After six months of follow-up, protein intake differed only by 0.07 g/kg/day between the two groups. The mean declines in GFR were 4.2 mL/min/year (95%CI;2.9 to 5.5) in LPD group and 3.7 (95%CI; 2.7 to 4.7) in LPD+KA group. Compared with LPD, paitients in LPD+KA group had reduced proteinuria (2.16±0.4 vs 3.56±0.6 g/day; p〈0.05). However, serum albumin and prealbumin levels did not change. Through further research we found that, after a median follow-up for six months, the urinary angiotensinogen:creatinine ratio in LPD patients was higher than in LPD+KA subjects (10.1 ±3.2 μg/g vs 5.8 ± 1.2 μg/g; p〈0.05);The urinary mRNA levels of the target genes nephrin, podocin and synaptopodin of podocyte were higher in the LPD group compared with LPD+KA(p〈0.05) in urinary sediment, and the expression of nephrin, podocin and synaptopodin mRNA positively correlated with serum creatinine (r=0.326, p = 0.04; r = 0.426, p = 0.03; r = 0.343, p = 0.001, respectively). In conclusion, compound α-keto acid tablet in combination with low protein diet (LPD+KA) is associated with amelioration of proteinuria, better reduction in the loss of kidney function compared with LPD alone meanwhile nutrition status remained well. The mechanism under these effects may be explained by the role of LPD+KA diet in reducing urine podocyte loss and lowering the angiotensinogen level in the urine.